2000
DOI: 10.1029/1999rg000066
|View full text |Cite
|
Sign up to set email alerts
|

What caused the glacial/interglacial atmospheric pCO2 cycles?

Abstract: Abstract. Fifteen years after the discovery of major glacial/interglacial cycles in the CO2 concentration of the atmosphere, it seems that all of the simple mechanisms for lowering pCO 2 have been eliminated. We use a model of ocean and sediment geochemistry, which includes new developments of iron limitation of biological production at the sea surface and anoxic diagenesis and its effect on CaCO 3 preservation in the sediments, to evaluate the current proposals for explaining the glacial/ interglacial pCO 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
486
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(511 citation statements)
references
References 157 publications
21
486
1
3
Order By: Relevance
“…Global warming could result in release of large amounts of GHGs, e.g., from melting permafrost or destabilized methane clathrates on continental shelves (43). Some of the largest warmings in the Earth's history and mass extinctions may be associated with such GHG releases (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…Global warming could result in release of large amounts of GHGs, e.g., from melting permafrost or destabilized methane clathrates on continental shelves (43). Some of the largest warmings in the Earth's history and mass extinctions may be associated with such GHG releases (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known as the "carbonate counter pump" effect. Additionally, it has been suggested that during the last glaciation, lower PIC:POC export ratio due to increased organic carbon export may have contributed to higher dissolution of the deep-ocean carbonate sediments, leading to a decrease in pCO 2 compared to the interglacial periods (Archer and Maier-Reimer, 1994;Archer et al, 2000;Sigman and Boyle, 2000). Therefore the PIC:POC ratio of exported particles is likely to have a significant impact on the atmosphere-ocean CO 2 fluxes from seasonal to geological timescales Sarmiento et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to account for the glacial CO 2 drop, large amounts of carbon must have been sequestered in the ocean. Different mechanisms have been suggested such as increased CO 2 solubility, greater Southern Ocean stratification and sea ice cover [Francois et al, 1997;Stephens and Keeling, 2000;Gildor et al, 2002], deepening of the lysocline [Archer et al, 2000] and increased marine export production due to either greater marine nutrient inventory [Broecker, 1982[Broecker, , 1998McElroy, 1983], or a higher Redfield ratio [Broecker, 1982;Omta et al, 2006], or an increase in iron availability in surface waters [Martin, 1990]. So far, however, model results and theoretical considerations [Archer et al, 2003] suggest that there does not seem to be a single mechanism that can explain the full magnitude of the glacial-interglacial atmospheric CO 2 changes as well as their timing.…”
Section: Introductionmentioning
confidence: 99%